Boron nitride nanotube-based amphiphilic hybrid nanomaterials for superior encapsulation of hydrophobic cargos. (December 2017) - Abu Saleh, Doaa; Niskanen, Jukka; Xue, Yanming; Golberg, Dmitri; Winnik, Françoise M.; Sosnik, Alejandro
Abstract: We report an organic-inorganic hybrid core-shell nanomaterial obtained by conjugation of an amphiphilic monomethoxy-poly(ethylene glycol)- b -poly(epsilon-caprolactone) diblock copolymer to hydroxylated boron nitride nanotubes (BNNTs). The extent of copolymer grafting reached 64% w/w, an exceptionally high value. The hybrid materials exhibit excellent physical stability in water and an outstanding loading capacity (31.3% w/w) for curcumin, a hydrophobic drug. Moreover, they present good compatibility with the Caco2 cell line, a model of intestinal epithelium. Our findings demonstrate the potential of multifunctional hybrid BNNTs to serve as a platform for complex amphiphilic nanoparticle architectures with improved features. Graphical abstract: Highlights: Organic–inorganic core-shell nanomaterials were produced by conjugation of a polymeric amphiphile to boron nitride nanotubes. The extent of copolymer grafting reached 64% w/w, an exceptionally high value. The hybrid nanomaterial exhibits outstanding loading capacity (31.3% w/w) for curcumin. The hybrid nanomaterial presents good compatibility with the Caco2 cell line.